Teachers' conceptions about the use of language variations and the practice of language prejudice in the classroom fundamental / As concepções de professores sobre o uso das variações linguísticas e a prática do preconceito linguístico em sala de aula no ensino fundamental - Silvio Nunes da Silva Júnior (Universidade Estadual de Alagoas, 2017)
This article aims to reflect on the concepts of elementary school teachers about the use of language variations and the practice of linguistic bias in the classroom, the research was conducted in a public school in the public sphere Maribondo- AL. The linguistic prejudice is constantly seen everywhere, always come from speakers of standard Portuguese (PP), with the victims speakers of Portuguese nonstandard (PNP), which most often are people with no education or else residents the countryside. The research corpus is composed of four questionnaires answered by teachers / informants. It was found that the conceptions of teachers were similar to each other, where they say they support the use of variations, as each region has its variations and this can never be changed. Was given to see that teachers do not practice the linguistic prejudice, just claim that the duty of the teacher in the school, the students are going to the dictates of normative grammar, making the school is facing the use of nonstandard language. This work is anchored in authors who work in the perspective of linguistic variation in elementary school areas that they are Bagno (2013), Bagno (2007), Bortoni-Ricardo (2004), among others.